The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1177/0269881198012003041
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin reuptake inhibitors in the treatment of affective disorders—III. Tolerability, safety and pharmacoeconomics

Abstract: The clinical use of tricyclic antidepressants (TCAs) is often complicated by toxicity and safety problems due to their effects on multiple mechanisms of action, many of which are unnecessary for therapeutic effect. The development of the selective serotonin reuptake inhibitors (SSRIs), with their selective mode of action, has resulted in a class of antidepressant drugs possessing an improved side-effect profile, while retaining good clinical efficacy. Their introduction into clinical practice has led to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(134 citation statements)
references
References 204 publications
4
126
0
4
Order By: Relevance
“…Thus, it would be incorrect to assume that individuals who are taking SRIs are characterized by reduced symptoms and should therefore also have reduced N300H. Moreover, consistent with the wide-spread localization of 5-HT signaling in the human brain (Cools et al, 2008), SRIs are known to have both anxiolytic and anxiogenic effects, with the anxiogenic effects being more pronounced at the beginning of treatment (Goldstein and Goodnick, 1998;Stahl, 1998;Trindade et al, 1998) often causing treatment discontinuation (Zanardi et al, 1996). In light of the positive relationship between anxiety and N300H , we hypothesize that SRIs by increasing brain-heart coupling produce anxiety-like side effects, which manifest at the beginning of treatment when anxiolytic effects of SRIs are not yet established (Stahl, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it would be incorrect to assume that individuals who are taking SRIs are characterized by reduced symptoms and should therefore also have reduced N300H. Moreover, consistent with the wide-spread localization of 5-HT signaling in the human brain (Cools et al, 2008), SRIs are known to have both anxiolytic and anxiogenic effects, with the anxiogenic effects being more pronounced at the beginning of treatment (Goldstein and Goodnick, 1998;Stahl, 1998;Trindade et al, 1998) often causing treatment discontinuation (Zanardi et al, 1996). In light of the positive relationship between anxiety and N300H , we hypothesize that SRIs by increasing brain-heart coupling produce anxiety-like side effects, which manifest at the beginning of treatment when anxiolytic effects of SRIs are not yet established (Stahl, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Dapoxetine is an SSRI and, as a new compound in this class, it merited special attention, given that other SSRI medications approved for the treatment of depression, anxiety, and other psychiatric conditions have infrequently been associated with reports of cardiovascular adverse events. [14][15][16] It was also important to assess the cardiovascular safety profile of dapoxetine because the proposed indication (i.e. PE) is not a life-threatening condition, and so syncope, albeit rare, might offset the clinical benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The most common adverse events were those associated with the gastrointestinal and nervous system organ classes, and reflected acute symptomatic events that were generally self-limiting and temporally related to dosing, reflecting tolerability rather than serious safety concerns. [26][27][28][29][30] Special attention was given to cardiovascularrelated safety issues since syncope has been reported with marketed SSRIs [14][15][16] and there were five cases of vasovagal syncope during dapoxetine phase I studies. During the initial two phase III clinical studies of dapoxetine, further cases of syncope were reported although, at the time, the occurrence appeared balanced among the placebo, 30 mg, and 60 mg treatment groups (2 of 872 [0.2%], 3 of 876 [0.3%], and 2 of 870 [0.2%] episodes, respectively).…”
Section: Phase III Randomized Placebocontrolled Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of SERT is a common feature that TCAs, SSRIs and SNRIs possess to elicit an antidepressant response; however, selective NE reuptake inhibitors (NRIs): reboxetine, atomoxetine and viloxazine have also been developed for depression and are prescribed for attentiondeficit/hyperactivity disorder (ADHD) [52][53][54]. SSRIs and SNRIs by virtue of their selective interactions at the SERT and NET exhibited an improved adverse effect profile; however, they were not without shortcomings [55,56]. These agents have failed to improve the efficacy and exhibit delayed onset, typically 4-6 weeks, of antidepressant response [57].…”
Section: Second-generation Antidepressantsmentioning
confidence: 99%